2018
DOI: 10.1590/1983-1447.2018.65127
|View full text |Cite
|
Sign up to set email alerts
|

Estresse ocupacional entre trabalhadores de saúde de um hospital universitário

Abstract: Resumo OBJETIVO Avaliar o estresse ocupacional entre trabalhadores de saúde de um hospital universitário. MÉTODOS Estudo transversal com trabalhadores de saúde de enfermagem e medicina de um hospital universitário da Região Sul do Brasil. Os dados foram coletados entre agosto de 2011 e agosto de 2012 por um questionário para caracterização e a Job Stress Scale. Realizou-se análise descritiva e univariada (Kruskal-Wallis). RESULTADOS Os participantes apresentaram alta demanda e alto controle do trabalho e ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
58

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 12 publications
2
30
0
58
Order By: Relevance
“…In this study, 71.8% of nursing professionals at the institution had some degree of exposure to stress and 30.6% of professionals were in a situation of high demand at work. This value is above that observed in similar studies (15,17,23) .…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…In this study, 71.8% of nursing professionals at the institution had some degree of exposure to stress and 30.6% of professionals were in a situation of high demand at work. This value is above that observed in similar studies (15,17,23) .…”
Section: Discussionsupporting
confidence: 47%
“…In a study conducted in a university hospital in the city of Rio de Janeiro, 56.5% of the nursing staff presented some level of stress (11) . In another study developed in a university hospital in the south of Brazil, 27.4% of the professionals presented occupational stress (23) . In a study conducted in the northeast region of Brazil, was found a 22.0% rate of exposure to stress among nursing professionals (19) .…”
Section: Discussionmentioning
confidence: 94%
“…this subject. 11,12 Regarding marital status, 64.8% of workers lived with a partner, a condition frequently observed in studies involving health professionals, with similar values, 12,13 or older. 14,15 This result may be associated with the participants' mean age.…”
Section: Independent Variables Regression Coefficients Pmentioning
confidence: 75%
“…Em comparação com algumas pesquisas anteriormente realizadas, a amostra estudada apresenta níveis semelhantes de estresse, fadiga e SB (p.ex., Borges, Argolo, & Baker, 2006;Chou, Li, & Hu, 2014;Mendonça, 2013;Mendonça et al, 2012). No entanto, outros estudos realizados com profissionais de saúde apresentaram resultados mais elevados (Lima, Farah, & Bustamante-Teixeira, 2018;Ribeiro, Marziale, Martins, Galdino, & Ribeiro, 2018;D. K. C. Silva et al, 2017).…”
Section: Discussionunclassified